2019
DOI: 10.1111/mec.15030
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the worldwide invasion of the Asian long‐horned beetle: A recurrent invasion process from the native area together with a bridgehead effect

Abstract: Retracing introduction routes is crucial for understanding the evolutionary processes involved in an invasion, as well as for highlighting the invasion history of a species at the global scale. The Asian long‐horned beetle (ALB) Anoplophora glabripennis is a xylophagous pest native to Asia and invasive in North America and Europe. It is responsible for severe losses of urban trees, in both its native and invaded ranges. Based on historical and genetic data, several hypotheses have been formulated concerning it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
77
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 86 publications
(144 reference statements)
7
77
1
Order By: Relevance
“…The ALB populations considered in this study are characterized by an overall low genetic diversity, similar to that reported with the same microsatellite markers for other invasive populations, e.g. in North America and Europe 20,22,23 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The ALB populations considered in this study are characterized by an overall low genetic diversity, similar to that reported with the same microsatellite markers for other invasive populations, e.g. in North America and Europe 20,22,23 .…”
Section: Discussionsupporting
confidence: 81%
“…Single Sequence Repeats (SSR), markers to explore the invasion genetics in the four ALB populations described above and in single ALB findings. The SSR markers previously developed specifically for ALB enabled to assess genetic diversity within and among invasive populations and offered a great potential to reconstruct history and the pathways of beetles’ spread using Approximate Bayesian computation analysis 2022 .…”
Section: Introductionmentioning
confidence: 99%
“…Xylophagous insects also presented a rather minor contribution, between 16 and 20% of the total species, although some species are important forest pests in Europe (Asian longhorned beetles, Anoplophora spp. ; Javal et al, 2019) and China (Dendroctonus valens and Sirex noctilio; Lu and Sun, 2017). An important difference between China and Europe consisted in the relative importance of the fruit feeders, a much larger proportion of non-native species being observed in China.…”
Section: Discussionmentioning
confidence: 99%
“…To date the most northern invasive population of ALB was in Finland and the most southern is in Lebanon, indicating that the species can tolerate a wide thermal range. The source of the invasive populations remains unclear due to complex genetic structure in the native range and potentially reticulated invasion pathways due to secondary spread from invasive populations [26,29].…”
Section: Introductionmentioning
confidence: 99%